2016
DOI: 10.1074/jbc.m116.716027
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemic Conditions Prime Cells for RIP1-dependent Necroptosis

Abstract: Necroptosis is a RIP1-dependent programmed cell death (PCD) pathway that is distinct from apoptosis. Downstream effector pathways of necroptosis include formation of advanced glycation end products (AGEs) and reactive oxygen species (ROS), both of which depend on glycolysis. This suggests that increased cellular glucose may prime necroptosis. Here we show that exposure to hyperglycemic levels of glucose enhances necroptosis in primary red blood cells (RBCs), Jurkat T cells, and U937 monocytes. Pharmacologic or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 34 publications
0
74
2
Order By: Relevance
“…In the present study we have demonstrated a novel shift from caspase-dependent extrinsic apoptosis to RIP1-dependent necroptosis in high glucose conditions. This is distinct from our previous work in which we showed hyperglycemic enhancement of cell death in response to specific stimuli of necroptosis 23 . In those experiments necroptosis was induced in normal and hyperglycemic conditions via artificial inhibition of apoptosis and was shown to increase in hyperglycemic conditions 23 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study we have demonstrated a novel shift from caspase-dependent extrinsic apoptosis to RIP1-dependent necroptosis in high glucose conditions. This is distinct from our previous work in which we showed hyperglycemic enhancement of cell death in response to specific stimuli of necroptosis 23 . In those experiments necroptosis was induced in normal and hyperglycemic conditions via artificial inhibition of apoptosis and was shown to increase in hyperglycemic conditions 23 .…”
Section: Discussioncontrasting
confidence: 99%
“…Our previous work established exacerbation of cerebral HI injury in hyperglycemic neonatal mice in a RIP1-dependent manner 23 . Based on our current work, we hypothesized that this may be the result of a shift from apoptosis to necroptosis in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that glycolysis regulates the production of ROS, and that ROS and AGEs are effector molecules of necroptosis. 11 WB results showed that the expression of RIP1, RIP3, and p-MLKL protein was increased at 22 mM; however, the expression of ATF4 was decreased ( Figure 3F and 3G). Put together, the results show that the high glucose (22 mM) affected the cell growth of osteoblast cells and induced cell necroptosis.…”
Section: High Glucose Promoted Necroptosis In Osteoblast Cellsmentioning
confidence: 96%
“…In addition, cellular death has also been reported in diabetic retinopathy, in age-related macular degeneration, and in programmed necrosis of the inflammatory cells, with all of them resulting from the action of AGEs, ROS, and MGO (Fig. 1 ) 6 , 9 .
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia is the trigger for the activation of several signaling pathways, and it represents a condition in which the cells become susceptible to necroptosis, apoptosis, and/or necrosis 6 . Both Type 1 and 2 diabetes mellitus (T1D and T2D) are metabolic disorders, apparently with distinct mechanisms, but with a significant loss of mass insulin-producing β-cells, due to cellular death 7 .…”
Section: Introductionmentioning
confidence: 99%